ADVISORY COMMITTEES FOR EVALUATION PROJECTS: บทบาทของคณะกรรมการที่ปรึกษาสำหรับการประเมินโครงการ - Buosonte, Rattana; Soontranont, Thanathat; Tunma, Piyarat; Hongsin, Phattaraporn; JirapunyaChot, Piyapat (Journal of Education and Innovation, 2023)
This main purpose of this article is presented on the Advisory Committees in Contract, Grant Evaluation Projects, and Advisory Groups for the evaluation in cultural diversity, group diversity, and community diversity. Evaluation is a tool to collect both quantitative and qualitative data in order to determine the proper behavior of facts internally by competing and presenting the data to inform the performance and accurately determined the experiment’s evaluation. The group of people or main subject in the project assessment is the advisory committee for the project assessment. The advisory committees have a joint role in suggesting guidelines for project assessment. advisory committee are responsible for the creation of content on various matters related to the assessment such as: the design of the evaluation project, data collection tools, different steps, analysis, interpretation of content data, and format for reporting the assessment results, etc. The roles and duties of the advisory committee for project assessment include stakeholder engagement, maximizing external credibility, political conciliation, promotion of methodological integrity, and promotion of use. This article offers a view on the advisory committee based on two articles are Advisory committees in contract and grant-funded evaluation projects by Paul W. Mattessich and Advisory groups for evaluations in diverse cultural groups, communities, and contexts by Barry B. Cohen.